The Social Uses of Literacy : Theory and Practice in Contemporary South Africa. - Prinsloo, Mastin (John Benjamins Pub. Co., 1996)
This book details the findings of a research project investigating the social uses of literacy in a range of contexts in South Africa. This approach treats literacy not simply as a set of technical skills learnt in formal education, but as social practices embedded in specific contexts, discourses and positions. What this means is made clear through a series of fine-grained accounts of social uses and meanings of literacy in contexts ranging from the taxi industry in Cape Town, to family farms, urban settlements and displacement sites, rural land holdings, and various sites during the 1994 ele.